2019
DOI: 10.22581/muet1982.1902.20
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment Analysis for Roman Urdu

Abstract: The majority of online comments/opinions are written in text-free format. Sentiment Analysis can be used as a measure to express the polarity (positive/negative) of comments/opinions. These comments/ opinions can be in different languages i.e. English, Urdu, Roman Urdu, Hindi, Arabic etc. Mostly, people have worked on the sentiment analysis of the English language. Very limited research work has been done in Urdu or Roman Urdu languages. Whereas, Hindi/Urdu is the third largest language in the world. In this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Starting from simple features then moved to their eight features set. It was concluded that these set of eight features have been used in text sentiment analysis for English language (13) .…”
Section: Feature Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…Starting from simple features then moved to their eight features set. It was concluded that these set of eight features have been used in text sentiment analysis for English language (13) .…”
Section: Feature Extractionmentioning
confidence: 99%
“…min_df : It is the minimum numbers of documents a word must be present in to be kept. Nor m: It is set to l2; to ensure all our feature vectors have a euclidian norm of 1. ngram_range: It is set to (1,2) to indicate that we want to consider both unigrams and bigrams. stop_words: It is set to "preprocessing variable (Which holds all the necessary stopwords for Urdu and Roman Urdu Language)" to remove all common pronouns ("a", "the", etc) to reduce the number of noisy features.…”
Section: Feature Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the researchers have worked on SA using languages other than Urdu. Few researchers have worked in Urdu SA [21]. Urdu corpus and lexicon are developed by researchers [22][23][24][25].…”
Section: Related Workmentioning
confidence: 99%
“…A very limited sentiment analysis work exists for Roman Urdu which can be classified into lexicon based [18], machine learning, and deep learning based approaches [19], [20], [21], [22]. Lexicon based approaches have low applicability over unseen data, and machine learning based approaches predominantly use bag-of-words based feature representation approaches which face the problem of data sparsity.…”
Section: Introductionmentioning
confidence: 99%